Developing English Material Based on Authentic Material For Vocational High School Students - Abdul Haris Sunubi (Journal of Research and Multidisciplinary, 2020)
The aim of this research is to design English material for vocational school to make the students proficient in both spoken, written, and prepare students to work in the field soon after graduating. There are some factors which have to be considered such teachers, media, and material. Materials take an important part in the process of teaching-learning. The material also helps the students to practice and give them exposure. Research design is Educational Research and Development (R&D). It is adapted from industry-based development model in which the results of the research will be taken to create new products or procedures. The subjects of this research were eleventh-grade students of fishery major in Vocational School Negeri Rea Timur academic year of 2019/2020. All the students were involved as the research subject, the class consisted of 20 students. There are 4 English teachers in Vocational School Negeri Rea Timur two civil servants and the other honorary teachers. The result of this research that most students of fishery study major at Vocational school Rea Timur (50%) use English only to read texts in English coursebook, worksheet and other learning sources. (17%) them to read the texts beyond English lessons such as advertisement, magazine, newspaper. (13%) of them to read the texts beyond English lessons such as advertisement, magazine, newspaper. Only a few of them use English as a means to read texts in English coursebook, worksheet and other learning sources (8%).